EXPLORING THE CRIMINAL IMPLICATIONS OF USING BLANK BILYET GIROS IN CONTRACT BREACHES IN INDONESIA - Rexy Mierkhahani; Anton Hendrik Samudra; Anastasia Suhartati Lukito (Universitas Syiah Kuala, 2023)
This article examines the criminal aspect of using blank bilyet giro (BG) as a payment method in breach of contract cases in Indonesia. It argues that such a practice could potentially constitute fraud, necessitating its differentiation from a mere contract breach. Utilising a doctrinal approach, underpinned by both statutory and conceptual analysis, it formulates a legal rationale for constructing a criminal case predicated on a contract breach involving a blank BG. Furthermore, it deliberates on the ramifications of this issue for business law and law enforcement practices. The primary objective of this article is to furnish pragmatic guidance for legal practitioners such as lawyers and investigators, while concurrently stimulating scholarly discourse.